Parámetros productivos y estabilidad oxidativa de yema de huevo en Coturnix japonica “codorniz” a la adición de Origanum vulgare “orégano” en la dieta - Loyaga Cortéz, Bruno Saúl (2019)
The aim of this research was to determine the effect of dietary oregano essential oil (OEO) at performance and oxidative stability; were evaluated 240 quails of 110 days old were divided into 4 groups. One of the groups was given the control diet with antibiotics (0.01% enramycin and 0.025% colistin sulfate) and other groups with 100, 150 and 200 mg/kg levels of supplementation of oregano essential oil supplements for 12 weeks. Quail performance and the oxidative stability of egg yolk with 0, 7 and 15 days of storage were determined. The results show that the diet supplemented with OEO 200 mg/kg exerts positive effects on feed intake in quail (p < 0.05), the control diet and the OEO diet 200 mg / kg were higher in egg production and feed conversion (p < 0.01), referring to egg weight and egg mass, no statistical differences were found (p > 0.05), finally the OEO diet 200 mg / kg obtained the best economic efficiency. Supplementation with AEO 100 mg / kg decreased lipoperoxidation in the quail egg yolk on days 0, 7 and 15 (p < 0.01), independently of the storage time. In conclusion, the OEO has a nutritional potential to reduce the oxidation of lipids in the egg system and also improve some productive parameters.